A business plan for GroW4ll, an end to end products and services for urban gardening in Malaysia - Lee, Hooi Ching (2021)
Agro 4 All Sdn. Bhd. (GroW4ll) is a social enterprise establishing in Malaysia by December 2020. GroW4ll delivers end to end services and products for urban gardening to Malaysian via physical urban gardens and online platforms in a mobile application. Creating uncontested market of digital platform to existing nurseries and urban gardens, GroW4ll offers additional services on maintenance support via subscription-based model for marketplace, content library and home services. The primary target market for GroW4ll are fast pace tech-savvy urbanites in the age range of 25 to 50 years old. GroW4ll is providing a “one stop solution for urban gardening portal for urbanites”.